2017
DOI: 10.1080/15384047.2016.1276132
|View full text |Cite
|
Sign up to set email alerts
|

Synergistic effect of cytokine-induced killer cell with valproate inhibits growth of hepatocellular carcinoma cell in a mouse model

Abstract: Objective: Long-term prognosis of hepatocellular carcinoma (HCC) remains poor owing to the lack of treatment options for advanced HCC. Cytokine-induced killer (CIK) cells are ex vivo expanded T lymphocytes expressing both NK-and T-cell markers. CIK cell therapy alone is insufficient for treating advanced HCC. Thus, this study aimed to determine whether treatment with CIK cells combined with valproic acid (VPA) could provide a synergistic effect to inhibit tumor growth in a mouse model of HCC. Methods: Upregula… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 27 publications
0
8
0
Order By: Relevance
“…In human hepatocytes, the ERK pathway can be activated by VPA exposure . Given that both melatonin and VPA have been reported to prevent tumor growth and progression in animal models of cancer , it would be interesting to determine the combinatorial effects in vivo in our future studies.…”
Section: Discussionmentioning
confidence: 99%
“…In human hepatocytes, the ERK pathway can be activated by VPA exposure . Given that both melatonin and VPA have been reported to prevent tumor growth and progression in animal models of cancer , it would be interesting to determine the combinatorial effects in vivo in our future studies.…”
Section: Discussionmentioning
confidence: 99%
“…Second, CIK cells could be stimulated by upregulating the expression of major histocompatibility complex (MHC) class I-related chain (MIC)-A and -B, which bind to natural killer group 2 member D (NKG2D) and activate CIK cells. Our group recently reported that histone deacetylase inhibitors such as suberoylanilide hydroxamic acid and valproate enhance the expression of MIC-A and -B in an epigenetic manner [ 45 ]; therefore, combination therapy with these agents could also be considered. Third, combination treatment with different types of adoptive immunotherapy such as dendritic cell vaccine could be utilized.…”
Section: Discussionmentioning
confidence: 99%
“…Few clinical studies have confirmed the role of CIKs in the maintenance therapy of advanced lung cancer patients. CIKs, alone or in combination with other therapies, have proven safe and efficient in clinical practice 22 24 , 29 , 30 . CIK cells consist of a heterogeneous cell population, with the primary population comprising CD3 + CD56 − and CD3 + CD56 + cells and a minor population of CD3 − CD5 + cells 13 .…”
Section: Discussionmentioning
confidence: 99%